FROM PHILOSOPHY TO NORMATIVE CONFIGURATION: A SCOPING REVIEW OF INDONESIAN COPYRIGHT LAW - Fajar Sugianto; Ellora Sukardi; Atsuko Yamamoto (Diponegoro Law Review, 2025)
The development of Intellectual Property Rights (IPR) is significantly shaped by John Locke’s theory of property, along with subsequent philosophical discourse, which provides a foundation for granting exclusive rights to creators and inventors. IPR aims to balance the protection of individual interests with the greater public good, while fostering innovation. In the Indonesian context, a comprehensive legal framework and effective enforcement mechanisms are crucial to maintaining this equilibrium, particularly within the domain of copyright law. This research investigates whether Indonesia’s copyright system reflects the philosophical foundations of intellectual property, examines the integration of these principles into legal norms, and evaluates their role in supporting the growth of the national creative economy. Using a scoping review methodology, the study reveals a strong alignment between philosophical principles of ownership and Indonesia’s legal framework. This alignment highlights the dual role of copyright law: protecting individual creators' rights while stimulating a thriving creative economy. Furthermore, the research underscores the importance of balancing the interests of creators, industries, and the public. The study also explores how the Indonesian government has updated copyright legislation to better protect and promote creative industries, acknowledging the significant role of copyright in economic development. Recent policy reforms, such as the restructuring of the National Collective Management Institute (LMKN) and the digitalization of royalty databases, demonstrate a commitment to harmonizing legal practices with philosophical ideals. These reforms reflect an evolving copyright system that adapts to global dynamics, addressing technological challenges while ensuring effective protection of intellectual property rights.